A final accounting : philosophical and empirical issues in Freudian psychology - Erwin, Edward, 1937- (Bradford book., 1996)
"More than a century has passed since Sigmund Freud began his groundbreaking work in psychoanalysis, yet there is no consensus about his legacy; instead, there is persistent disagreement not only about Freud's reputation and place in history but about the proper standards to use in evaluating his theory and therapy." "This book develops epistemological standards for Freudian psychology and provides a comprehensive evaluation of, and possibly final verdict on, Freud's theory and therapy. Unlike any other evaluation published to date, it contains a systematic discussion of both the Freudian experimental and non-experimental evidence and the proper standards for interpreting the evidence."--Jacket